Red blood cells radial dispersion in blood flowing through microchannels: the role of temperature - Pinho, Diana (2016)
The behavior of suspensions of individual blood cells, such as red blood cells (RBCs), flowing through microvessels and microfluidic systems depend strongly on the hematocrit (Hct), microvessel topology and cell properties. Although it is well known that blood rheological properties are temperature dependent, to the best of our knowledge no work has studied the role of the temperature on the RBCs dispersion. A powerful way to investigate this latter effect is through a high-speed video microscopy system, which provides detailed flow measurements of each individual RBC. Hence, the effect of temperature on the RBCs dispersion flowing through a 100μm glass capillary was examined by means of a confocal micro-PTV system. Hundreds of labeled RBCs were tracked at moderate Hct (12%) and at four different temperatures, i.e., 25°C, 32°C, 37°C and 42°C. The results yielded an enhancement of the RBCs diffusion as the temperature increases. Hence, our findings show that RBCs radial dispersion is temperature dependent and as a result the temperature should not be ignored in future blood flow studies. We believe that this finding is important for a better understanding of blood mass transport mechanisms under both physiological and pathological conditions.